2014
DOI: 10.1177/2150135114528721
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Three-Dimensional Printing Technology to Assess the Feasibility of High-Fidelity Synthetic Ventricular Septal Defect Models for Simulation in Medical Education

Abstract: It is feasible to use present-day 3D printing technology to create high-fidelity heart models with complex intracardiac defects. Furthermore, this tool forms the foundation for an innovative, simulation-based educational approach to teach students about CHD and creates a novel opportunity to stimulate their interest in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 13 publications
1
115
1
6
Order By: Relevance
“…3D-printed cardiac models generated from the medical images of real patients are likely to reduce misinterpretations of pathological structures. Costello et al [21,22] printed various VSD models to teach 52 medical students and found a significant improvement in structural conceptualization. 3D-printed cardiac models improve the spatial orientation of medical students [23].…”
Section: Medical Educationmentioning
confidence: 99%
“…3D-printed cardiac models generated from the medical images of real patients are likely to reduce misinterpretations of pathological structures. Costello et al [21,22] printed various VSD models to teach 52 medical students and found a significant improvement in structural conceptualization. 3D-printed cardiac models improve the spatial orientation of medical students [23].…”
Section: Medical Educationmentioning
confidence: 99%
“…This is particularly true in congenital heart disease, where a wide spectrum of severity is observed within each type of cardiac defect. This wide spectrum of severity makes learning about these lesions complex to trainees, and it is encouraging that evidence suggests 3D models aid in learning about congenital heart defects and their clinical sequelae for trainees of various levels [28,29]. Complex anatomical concepts in congenital heart disease such as malalignment-type ventricular septal defects, double-outlet right ventricle, and the spectrum of heterotaxy syndromes can be demonstrated in a hands-on, interactive environment.…”
Section: Educational Value Of 3d Heart Modelsmentioning
confidence: 95%
“…nurses or students); the use of 3D-printed models for training has been used in other areas of medicine [34] and also, in CHD, in a study that focused on the appreciation of ventricular septal defects in a cohort of medical students [35] suggesting the beneficial use of 3D models for better appreciation of the defect.…”
Section: Outlook and Considerations For Future Researchmentioning
confidence: 99%